IMPLEMENTATION OF AGILE GOVERNMENT IN ESAKIP IN THE CITY OF YOGYAKARTA - Nurhidayanti, Nadia Tri; Mutiarin, Dyah; Saputro, Muhammad Noor Cahyadi Eko (Prosiding University Research Colloquium, 2023)
The research was conducted with the aim of knowing the implementation of the principles of agile government accountability through the application of E-SAKIP (Electronic Government Agency Performance Accountability System) in the City of Yogyakarta. This application is a system that aims to facilitate the process of monitoring and controlling government performance. The principle of agile governance is government that is fast, precise, effective and efficient in providing public services by using increasingly advanced technological developments. In implementing SAKIP, the City Government of Yogyakarta has won an award with the AA predicate. This research was conducted in December 2022 until January 2023. The type of research used is qualitative research by examining data on the implementation of E-Sakip by analyzing previous documents collected and stated in the form of words which are then arranged into sentences and also used secondary data as a data source. With this research, it is hoped that it can be one of the efforts to continue to improve public services to the community.